Машины ударного действия для разрушения горных пород - Лобанов Д. П. Дмитрий Петрович; Горавиц В. Б. Виктор Борисович; Фонберштейн Е. Г. Ефим Григорьевич; Шендеров В. И. (Москва, Недра, 1983)
Авт. указаны на обороте тит. л.